1999
DOI: 10.1161/01.res.84.4.384
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Implants Inhibit Intimal Hyperplasia After Porcine Angioplasty

Abstract: Abstract-The perivascular implantation of tissue-engineered endothelial cells around injured arteries offers an opportunity to study fundamental vascular physiology as well as restore and improve tissue function. Cell source is an important issue because the ability to implant either xenogeneic or allogeneic cells would greatly enhance the clinical applications of tissue-engineered grafts. We investigated the biological and immunological responses to endothelial cell xenografts and allografts in pigs 4 weeks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 55 publications
8
91
0
Order By: Relevance
“…Part of the reason for this is that primary nonfunction is a poorly understood, multifactorial process that is unlikely to respond to single-drug therapy. An exciting alternative approach (cellbased therapy) has been pioneered by Nugent et al (33,111); it involves embedding specific cell types (e.g., endothelial cells) into a perivascular Gelfoam cuff. These cells then could produce an array of mediators that hopefully would mimic the two main functions of endothelial cells (promote vascular dilation and inhibit neointimal hyperplasia).…”
Section: Promoting Native Avf Maturationmentioning
confidence: 99%
“…Part of the reason for this is that primary nonfunction is a poorly understood, multifactorial process that is unlikely to respond to single-drug therapy. An exciting alternative approach (cellbased therapy) has been pioneered by Nugent et al (33,111); it involves embedding specific cell types (e.g., endothelial cells) into a perivascular Gelfoam cuff. These cells then could produce an array of mediators that hopefully would mimic the two main functions of endothelial cells (promote vascular dilation and inhibit neointimal hyperplasia).…”
Section: Promoting Native Avf Maturationmentioning
confidence: 99%
“…The importance of the endothelium is supported clinically by the improvement Zilla et al showed in prosthetic graft patency and function after EC seeding compared to unseeded grafts [94,95]. This is probably the most obvious way to promote a confluent endothelium, and it can be used at sites of intimal disruption [96] or on prosthetic grafts as reviewed by Parikh and Edelman in 2000 [97]. We have been able to promote endothelialization of prosthetic grafts exceeding 30 cm in length without cell seeding through the localized delivery of the potent angiogen FGF-1 in a fibrin glue delivery vehicle to prosthetic vascular grafts [98] (Fig.…”
Section: Promoting a Functional Endotheliummentioning
confidence: 97%
“…Initial experimental studies have documented a beneficial effect of endothelial cell loaded gel-foam wraps in porcine models of AV fistula and graft stenosis [195][196][197][198] . A recent Phase II study ("V-HEALTH") was able to demonstrate technical feasibility and safety in hemodialysis patients who received a "VascugelÂŽ" wrap loaded with treated human aortic endothelial cells at the time of AVF or AVG placement 97 .…”
Section: Endothelial Cell Loaded Gel Foam Wrapsmentioning
confidence: 99%